The Association Between Bifid Median Nerve and Carpal Tunnel Syndrome: Is it Really a Risk Factor? - Mahmut DUYMUŞ; Güneş ORMAN; Serkan ÖZBEN; Nergiz HÜSEYİNOĞLU and Alper Murat ULAŞLI (Archives of Rheumatology, 2014)
Objectives: This study aims to determine the bifid median nerve (BMN) frequency in patients with carpal tunnel syndrome (CTS) and to investigate the possible association between CTS and BMN in this patient population. Patients and methods: A total of 194 wrists of 131 patients in whom CTS was diagnosed clinically and electrophysiologically and 73 healthy volunteers without any symptom or sign of CTS were examined with ultrasonography. Results: Bifid median nerve was detected in 22 wrists (11.3%) in CTS group and 15 wrists (10.2%) in the control group. There was no statistically significantly difference in the incidence of BMN among patients with CTS and healthy volunteers (p=0.891). Conclusion: Our study results showed that the incidence of BMN was similar among CTS patients and healthy volunteers. Therefore, we conclude that BMN may not be a predisposing factor for CTS.